The Mobilisasi Dini terhadap Tekanan Darah, Denyut Nadi dan Saturasi Oksigen pada Pasien Congestive Heart Failure - Nurfitriawaty, Risma; Bangun, Argi Virgona (Journal of Telenursing (JOTING), 2024)
The study aims to analyze the effectiveness of early mobilization on blood pressure, pulse rate, and oxygen saturation of CHF patients. The research method uses a quasi-experiment, pretest-posttest with a control group design. The results of the paired t-test before and after early mobilization in the intervention group showed an increase in systolic blood pressure (t = 13.2 mmHg, p-value = 0.000), diastolic blood pressure (t = 12.6 mmHg, p-value = 0.000), pulse rate (t = 16.1 times/minute, p-value = 0.000), and oxygen saturation (t = 11.8%, p-value = 0.000), while in the control group there was an increase in systolic blood pressure (t = 5.75 mmHg, p-value = 0.000), diastolic blood pressure (t = 5.99 mmHg, p-value = 0.000), pulse rate (t = 5.51 times/minute, p-value = 0.000), and oxygen saturation (t = 5.59%, p-value = 0.000), The results of the Independent t-test after early mobilization showed an increase in systolic blood pressure (t = 6.49, p-value = 0.000), and oxygen saturation (t = 4.90, p-value = 0.000) in the intervention group compared to the control group, however, there was no significant difference between the two groups in diastolic blood pressure (t = 1.17, p-value = 0.24), and pulse rate (t = 0.24, p-value = 0.80), Conclusion, early mobilization in CHF patients is more effective in increasing systolic blood pressure and oxygen saturation compared to standard care, although it has no significant effect on diastolic blood pressure and pulse rate. Keywords: CHF, Early Mobilization, Pulse, Oxygen Saturation, Blood Pressure